Can online platforms promote women-led exporting firms? - Jennifer P. Poole; Christian Volpe Martincus (Inter-American Development Bank (IDB), 2023)
How can policymakers promote women-led exporting firms? In this paper, we study the role of online business platforms to reduce informational barriers to exporting for women entrepreneurs. We hypothesize that, if the costs associated with accessing digital platforms are more symmetric across gender than traditional trade costs, digital trade platforms can play an important role in making trade more gender equal. To assess this hypothesis, we combine information on firms' participation in ConnectAmericas, a free and purely informational online platform, and detailed firm-level export data of a developing country over a long period. We find that participation in this platform is associated with a significantly larger increase in exports for women entrepreneurs than for men-managed firms in otherwise identical products and destinations. Given existing evidence on the role of women-managed businesses in reducing gender earnings inequality, these results suggest that policies which encourage women participation in online environments, to reduce the informational barriers associated with operating in foreign markets, have the capacity to promote gender equality more broadly.
Keywords: F13; F14; J16; L15; L26; 330; Online Platforms; Firms; Exports; Gender; Trade Promotion; Latin America